Kajian Menambahbaik Turutan Pembinaan Rumah Dua Tingkat - Rasyid, Mohd sofian; Bin Ismail, Isham (Recent Trends in Civil Engineering and Built Environment, 2022)
Various challenges have been faced especially in the form of online learning while facing Covid 19 pandemic. Learning for Construction Engineering course requires detailed description to facilitate students to understand the actual construction sequence at the construction site. This study has improved the 3D animation videos of the construction sequence by referring to the syllabus of the Construction Engineering course and the actual construction at the construction site. The production of this animation video module uses a combination of three free software namely 3D Google SketchUp, IBM Watson text to speech and Filmora. This study has produced nine animations completed e-modules for the construction process of two-storey bungalows and only three of the video animation improvements are discussed in this research paper. In conclusion, the lack of animation video for house construction available on YouTube has been improved and meets the needs of the actual construction process at the construction site.